Estudo fitoquímico de Astronium graveolens (Anacardiaceae) e da ação de seus constituintes sobre o formigueiro de Atta sexdens rubropilosa - Villari, Maria Fernanda Martinez (2011)
Brazil has a rich fauna and flora, for these reasons it is called as mega-diverse country. This diversity enables the isolation and identification of substances that become promising in several areas and an example is the insecticidal activity of various substances in agriculture. This study presents the identification of volatiles from leaves, the phytochemical study and insecticidal and fungicidal test of fractions of organic extracts of Astronium graveolens (Anacardiaceae) that belong to the Order Sapindales. Among the fractions tested against leaf-cutting ants (Atta sexdens rubropilosa) and their symbiotic fungus, Leucoagaricus gongylophorus, ethyl acetate fractions of ethanolic extracts of roots, stems and branches showed good activities. In parallel was evaluated the action of those fractions against Spodoptera frugiperda, however, those fractions did not showed promising activities. Phytochemical study of ethyl acetate fractions resulted in the isolation of 11 secondary metabolites, two flavonoids: 5,3',4'-trihydroxy-7-methoxyflavone and myricetin-3-O-_-L-rhaminosídeo, three phenolic compounds: epigallocatechin methyl ester, 5-O-caffeoylquinic acid, 3- O-galoil-5-cafeoilchinic acid (inedited); six dimeric chalcones, (7S,8"R)-(2',4,4',5, tetrahydroxychalcone-(2_7",8_8 ')-2' ,4",4"'-trihydroxy-7",8"-dihydrochalcone; (7R,8S,7"S,8"R)-2',4,4',5,7-pentahydroxy-7,8-dihydrochalcone-(2_7",8_8")- 2 ',4",4"'-trihydroxy-7",8"dihydrochalcone; (7S,8R,7 S,8 S)-2',4,4',5,7-pentahydroxy- 7,8-dihydrochalcone-(2_7",8_8")-2 ',4",4"'-trihydroxy-7",8"-dihydrochalcone; rel- (7S,8S,7"S,8S)-tetrahydro-7,7''-bis-(4-hydroxyphenyl)-7,7''(furandil)-8,8,2.4''- dihydroxiphenyl;4,5,4 dihydroxy-7,2 -oxo-chalcone-(2_7 ,8_8 )-2 ,4 ,4 ,2 ,4 - trihydroxychalcone; 4,4 dihydroxy-7,2 -oxo-chalcone-(2_7 ,8_8 )-2 ,4 ,2 ,4 - tetrahydroxychalcone . The dimeric chalcones are new to the genera and, except first one, in the literature.